One October tragedy in Las Vegas: An overview of tourists' perceptions - Mehmet Erdem; Saeed Hasanzadeh; Billy Bai (Journal of Tourism, Heritage & Services Marketing, 2020)
Purpose: This study seeks to examine Las Vegas visitors' perception about security in Las Vegas and the perceived risks associated with traveling to Las Vegas following the One October mass shooting. It also aims to explore potential Las Vegas visitors 'attitudes towards the proactive security measures implemented by Las Vegas resorts after the One October tragedy. Methods: The study is descriptive in nature. The data was collected through a web-based survey that comprised a national sample of 414 adults from the United States. Results: The results indicate that despite the tragic One October mass shooting in Las Vegas and the associated media coverage, security is not a major concern for visitors to Las Vegas. The findings of this study also suggest that Las Vegas visitors approve of existing and emerging security procedures. Implications: Findings point out to an opportunity to capitalize on the perceived enhanced security measures in Las Vegas and to put emphasis on addressing financial risk concerns via marketing and public relations campaigns.
Keywords: L83; M31; Z33; 330; Las Vegas; security; tourism; tourist behavior; resorts